THE ABSENCE OF WOMEN’S POWER IN POLITICAL COMMUNICATION IN DKI JAKARTA GOVERNOR ELECTION - Umaimah Wahid (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2016)
The study about the absence of women representation in DKI (Special District of Capital Jakarta) Jakarta governor election 2012 aims at mapping political power in DKI Jakarta Province. It also elaborates, criticizes and evaluates political parties’ supports and DKI Jakarta Province in efforts to enhance women consciousness to participate in political practice. This research uses political communication theory focusing on political understanding and women as political candidate, power and hegemony concept of women political realities as well as radical feminism. Critical paradigm with qualitative approach, case study method and feminist research are utilized for this research. The results indicate that the women’s power in the politics of DKI Jakarta compared to men who are clearly dominant. None of the governor candidates and governor deputy are women since there was not any individual who nominate themselves or being promoted by the political parties. Naturally, women have a great opportunity to lead Jakarta; however they need tremendous efforts to strengthen themselves and bolster their quality so that they can decrease domination of the one group of society. In addition, the supports from political parties are significant to develop women political society. Women need to change this situation by conducting the struggle and build a strong network for the development of the power of women in politics. Large is the struggle for women to Jakarta in the future have the ability and courage to dare to be part of the practical politics of Jakarta as the head of the region in the future.